2022
DOI: 10.1088/1475-7516/2022/08/038
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Dirac vs. Majorana neutrinos: a cosmological probe

Abstract: Cosmic background neutrinos (CνB) helicity composition is different for Dirac or Majorana neutrinos making detectors based on CνB capture sensitive to the nature of neutrinos. We calculate, for the first time, the helicity changes of neutrinos crossing dark matter fields, to quantitatively calculate this effect on the capture rate. We show that a fraction of neutrinos change their helicity, regardless of them being deflected by a void or a dark matter halo. The average signal from the 100 most massive voids or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In our previous work [9], we demonstrated that the neutrino velocity field is locally deflected over time and, indeed, the helicity content of Dirac neutrinos is modified. In that work, we assumed that different neutrinos mass eigenstates were equally populated, but, in reality, this is not the case: different neutrinos masses have different velocity fields so will suffer different deflection when falling into the same gravitational potential.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In our previous work [9], we demonstrated that the neutrino velocity field is locally deflected over time and, indeed, the helicity content of Dirac neutrinos is modified. In that work, we assumed that different neutrinos mass eigenstates were equally populated, but, in reality, this is not the case: different neutrinos masses have different velocity fields so will suffer different deflection when falling into the same gravitational potential.…”
Section: Introductionmentioning
confidence: 77%
“…As the Universe is clustered and non-linear gravitational structures exist, neutrinos will suffer a deflection angle when falling into a gravitational potential. This means that the helicity content of the C ν B is modified by gravity in the case that neutrinos are Dirac particles, which results in a decrease of the Dirac capture rates for experiments based on cosmic background neutrinos capture as Ptolemy [9,11]. Capture rates depend on neutrino mass and neutrinos helicity states densities.…”
Section: Deflection Angle Distribution Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations